2021
DOI: 10.12703/r/10-52
|View full text |Cite
|
Sign up to set email alerts
|

Novel and atypical pathways for serotonin signaling

Abstract: Serotonin (5-HT) appeared billions of years before 5-HT receptors and synapses. It is thus not surprising that 5-HT can control biological processes independently of its receptors. One example is serotonylation, which consists of covalent binding of 5-HT to the primary amine of glutamine. Over the past 20 years, serotonylation has been involved in the regulation of many signaling mechanisms. One of the most striking examples is the recent evidence that serotonylation of histone H3 constitutes an epigenetic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…Surprisingly, MDMA also activates sigma-1 receptors with a behavioral effect similar to DMT in animal models [79]. In conclusion, serotonergic and dissociative (NMDAantagonist) psychedelics act in cooperation at the cellular level [74]. These mechanisms are highly relevant in PTSD.…”
Section: Reconsolidation Of Engrams and The Cellular Mechanism Of Psy...mentioning
confidence: 91%
See 3 more Smart Citations
“…Surprisingly, MDMA also activates sigma-1 receptors with a behavioral effect similar to DMT in animal models [79]. In conclusion, serotonergic and dissociative (NMDAantagonist) psychedelics act in cooperation at the cellular level [74]. These mechanisms are highly relevant in PTSD.…”
Section: Reconsolidation Of Engrams and The Cellular Mechanism Of Psy...mentioning
confidence: 91%
“…5-HT2A agonism is a common mechanism of serotonergic psychedelics, including psilocybin ("magic mushroom", 4-phosphoryloxy-N, N-dimethyltryptamine) and Ayahuasca (N,N-dimethyltryptamine, DMT) [60]. Lysergic acid diethylamide (LSD) is only a partial agonist on 5-HT2A, promoting beta-arrestin activation and slow receptor desensitization, but a full agonist at 5-HT1A and several dopamine receptors (D1, D2, and D4) [53,74].…”
Section: Reconsolidation Of Engrams and The Cellular Mechanism Of Psy...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pantothenate and pyridoxamine were positively correlated with B. subtilis strain, which may enhance the biosynthesis of vitamins and cofactors in kinema, imparting health-promoting benefits to consumers. Serotonin, a neurotransmitter (Sahu et al, 2018), was found to be correlated with the neuroactive ligandreceptor interaction via predictive function, and it could control the signaling pathways either intracellularly by serotonylation or extracellularly via membrane receptors (Bockaert et al, 2021). Swainsonine predicted in KEGG database was also detected in metabolomics analysis in kinema samples, which is involved in the biosynthesis of tropane, piperidine, and pyridine alkaloid (Li and Lu, 2019).…”
Section: Validation Of Metabolomics With Metagenomicsmentioning
confidence: 99%